An Introduction to scientology an exclusive interview with L. Ron Hubbard - Hubbard, L. Ron (La Fayette Ron) 1911-1986 (Golden Era Productions, 2006)
An interview with L. Ron Hubbard in which he discusses the basic principles of scientology.